Shaun Gladwell (five texts) - Messham-Muir, Kit (Sherman Contemporary Art Foundation, University of New South Wales Galleries, 2015)
Shaun Gladwell – The Lacrima Chair, Sydney: Sherman Contemporary Art Foundation, (2015): 24-25, 46-47, 82-83, 120-121, 144-145